2014
DOI: 10.1063/1.4896135
|View full text |Cite
|
Sign up to set email alerts
|

Field-assisted patterned dissolution of silver nanoparticles in phosphate glass

Abstract: Articles you may be interested inPeriodic nanostructuring of Er ∕ Yb -codoped IOG1 phosphate glass by using ultraviolet laser-assisted selective chemical etchingPoling-assisted bleaching of soda-lime float glasses containing silver nanoparticles with a decreasing filling factor across the depth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…The observed decrease of LSPR intensity and blue-shift of LSPR are similar to those reported in [49], where the authors demonstrated laser-controlled dissolution of Au NPs embedded in soda-lime glass. Note, it is hardly possible to dissolve Ag NPs in glass only by heat treatment, at temperature ∼300 • C the dissolution additionally requires the application of a high, ∼1 kV, DC voltage [50][51][52].…”
Section: Anps Formation Studiesmentioning
confidence: 99%
“…The observed decrease of LSPR intensity and blue-shift of LSPR are similar to those reported in [49], where the authors demonstrated laser-controlled dissolution of Au NPs embedded in soda-lime glass. Note, it is hardly possible to dissolve Ag NPs in glass only by heat treatment, at temperature ∼300 • C the dissolution additionally requires the application of a high, ∼1 kV, DC voltage [50][51][52].…”
Section: Anps Formation Studiesmentioning
confidence: 99%
“…Более высо-кие концентрации активного вещества (ионов редкоземельных элементов), которые могут быть достигну-ты в фосфатных стеклах, обеспечивают большее усиление на единицу длины и, таким образом, позволя-ют уменьшить размеры устройства и обеспечить высокую выходную мощность. Кроме того, фосфатные стекла имеют низкие оптические потери в ближней инфракрасной области, а также могут быть модифи-цированы с помощью ионного обмена для формирования волноводов [14].…”
unclassified